Induction of Progenitor Exhausted Tissue-Resident Memory CD8+ T Cells Upon Salmonella Typhi Porins Adjuvant Immunization Correlates With Melanoma Control and Anti-PD-1 Immunotherapy Cooperation - León-Letelier, Ricardo A.; Castro-Medina, Daniel I.; Badillo-Godinez, Oscar; Tepale-Segura, Araceli; Huanosta-Murillo, Enrique; Aguilar-Flores, Cristina; De León-Rodríguez, Saraí G.; Mantilla, Alejandra; Fuentes-Pananá, Ezequiel M.; López-Macías, Constantino; Bonifaz, Laura C. (Frontiers in Immunology, 2020)
Immunotherapy has improved the clinical response in melanoma patients, although a relevant percentage of patients still cannot be salvaged. The search for the immune populations that provide the best tumor control and that can be coaxed by immunotherapy strategies is a hot topic in cancer research nowadays. Tumor-infiltrating TCF-1+ progenitor exhausted CD8+ T cells seem to grant the best melanoma prognosis and also efficiently respond to anti-PD-1 immunotherapy, giving rise to a TIM-3+ terminally exhausted population with heightened effector activity. We tested Porins from Salmonella Typhi as a pathogen associated molecular pattern adjuvant of natural or model antigen in prophylactic and therapeutic immunization approaches against murine melanoma. Porins induced protection against melanomas, even upon re-challenging of tumor-free mice. Porins efficiently expanded IFN--producing CD8+ T cells and induced central and effector memory in lymph nodes and tissue-resident (Trm) T cells in the skin and tumors. Porins induced TCF-1+ PD-1+ CD8+ Trm T cells in the tumor stroma and the presence of this population correlated with melanoma growth protection in mice. Porins immunization also cooperated with anti-PD-1 immunotherapy to hamper melanoma growth. Importantly, the potentially protective Trm populations induced by Porins in the murine model were also observed in melanoma patients in which their presence also correlated with disease control. Our data support the use of cancer vaccination to sculpt the tumor stroma with efficient and lasting Trm T cells with effector activities, highlighting the use of Porins as an adjuvant. Furthermore, our data place CD8+ Trm T cells with a progenitor exhausted phenotype as an important population for melanoma control, either independently or in cooperation with anti-PD-1 immunotherapy.